Epidemiological and correlational investigation of the reasons for requesting inter-hospital transfer of patients in Gilan province under the guidance of the Medical Care Monitoring Center in 1401 - Seyed Mohammad Mehdi Baki Hashemi (Tehran University of Medical Sciences, 2023)
Background and purpose: Inter-hospital transfer refers to the transfer of patients to receive diagnostic, therapeutic and paraclinical services that can prevent more injuries or more effective treatment. The present study was designed with the aim of collecting and analyzing information related to sent patients and identifying the factors that cause the transfer of patients. Methods: This cross-sectional study was conducted on 11,362 patient referral forms registered at Gilan University of Medical Sciences. Data were analyzed by Spss statistical software version 22 and Chisquer statistical test. Results: The amount of patient transfer requests in 1401 compared to 1400 has increased by 9%. There is a relationship between the demand for transfer of patients with inappropriate distribution of specialized human resources, lack of demand feedback mechanisms, ineffective planning of nursing staff and residency of doctors in the hospital of origin, inefficient management of resources and equipment, lack of diagnostic, medical and pharmaceutical facilities, as well as with the seasons of the year. There is significant (p>0.05). There is a significant relationship between non-acceptance of patients and the lack or lack of beds needed by the patient in the destination hospital (p<0.05). Conclusion: Improper distribution of specialized manpower according to the needs of the region, ineffective planning of resident guards, inefficient management have been identified as the main reasons for the demand for patient transfer. Forming a special working group to identify, evaluate, plan and monitor the removal of obstacles in a centralized manner and forming quality improvement circles can be a solution.